A review of energy management systems for smart grids - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2015)
Technology is advancing every day. These developments are accelerating the industrialization of energy. Electricity demand is rapidly increasing. Therefore, effective use of the available energy is a very important issue. Smart Grid allows the management of energy and real-time balance between electrical energy supply and demand sides. In this study, we investigate energy management systems for smart grids. © 2015 IEEE.
Keywords: energy management; smart grid